2017
DOI: 10.1016/j.ijscr.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Unstable thoracic spine fracture with aortic encroachment: A potentially fatal association and a suggested treatment

Abstract: HighlightsThe association of unstable spinal fractures and pending aortic injuries is a therapeutic dilemma.Inappropriate treatment can lead to catastrophic consequences.A multidisciplinary, case-by-case evaluation is mandatory.Vascular lesions must be treated first.We suggest “best but safest” procedure sequence: endovascular aortic repair and then posterior spinal cord reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Thoracic spine fractures are common in trauma [1,2]. Blunt aortic injury (BAI) is considered as a rare comorbidity in patients with thoracic spine fractures, only reported as a sporadic case [10][11][12][13][14][15]. The coexistence of traumatic thoracic fractures with BAI were potential catastrophic and BAI is an easily missed diagnosis in this case due to lack of understanding of this combined injury.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Thoracic spine fractures are common in trauma [1,2]. Blunt aortic injury (BAI) is considered as a rare comorbidity in patients with thoracic spine fractures, only reported as a sporadic case [10][11][12][13][14][15]. The coexistence of traumatic thoracic fractures with BAI were potential catastrophic and BAI is an easily missed diagnosis in this case due to lack of understanding of this combined injury.…”
Section: Discussionmentioning
confidence: 87%
“…While several papers have described the association of spinal fractures with aortic injury, most of them were case reports, autopsy study and literature review case series [10][11][12][13][14][15]. Two retrospective studies reported the correlation between spinal fractures and BAI by first selecting patients with BAI, and then studying these patients for concomitant spine fractures [23,24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few cases of BTAI with traumatic spinal injuries have been reported in the literature such as that by Fattahi et al [4], who described a hyperextension thoracic spine fracture complicated by paraplegia, aortic dissection, and right hemothorax requiring ICD tube insertion. Cultrera et al [5] described a compression/distraction spinal fracture complicated by aortic encroachment without wall disruption. Bashir et al [6] described an aortic laceration following a T10 vertebral body fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The EMBASE, PubMed, and Web of Science databases were searched using the terms "blunt thoracic aortic injury" and "thoracic fracture" to identify reports of blunt thoracic aortic injury as a result of thoracic fracture. The details of the reported identified (2,(4)(5)(6)(7)(8)(9)(10)(11) are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%